Fragility, Conflict and Migration (FCM) and National Policies and Strategies for Food, Land and Water Systems Transformation (NPS): Joint Initiative Seminar on Building Resilience Against Food Crises in Nigeria - Carrillo, Lucia; Kosec, Katrina; Omobolanle, Onilogbo; Smart, Jenny; Ambler, Kate; Andam, Kwaw S. (CGIAR System Organization, 2023)
On May 12 in Abuja, Nigeria, two CGIAR initiatives – Fragility, Conflict, and Migration (FCM) and National Policies and Strategies (NPS) – brought together policymakers, researchers, and representatives from the private sector and civil society to discuss how to advance food systems resilience amid crises while empowering women and youth, in the context of Nigeria. The workshop featured presentations from six other CGIAR research initiatives working in Nigeria and fostered lively discussions. Participants delved into cutting-edge research outcomes, identifying evidence gaps and potential collaborative avenues.